Peeling and Multi-critical Matter Coupled to Quantum Gravity - Harris, MG; Wheater, J (1999)
We show how to determine the unknown functions arising when the peeling decomposition is applied to multi-critical matter coupled to two-dimensional quantum gravity and compute the loop-loop correlation functions. The results that $η=2+2/(2K-3)$ and $ν=1-3/2K$ agree with the slicing decomposition, and satisfy Fisher scaling.